Systematic Literature Review: Research on Martial Arts Competition Using Vos Viewers in the 2018-2022 Google Scholar Database - Putu Citra Permana Dewi; Diah Primi Paramita; Qory Jumrotul Aqobah; Lesmana; Moch. Ali Akbar; Johaidah Mistar; Yasep Setiakarnawijaya (Gladi : Jurnal Ilmu Keolahragaan, 2023)
Martial arts competition is a sport of self-defense skills that employs the ability to defend oneself, repel attacks and ultimately attack enemies, with or without weapons. This study uses a descriptive quantitative method with a bibliometrics approach. The research data used for scientific journals or articles spanning 2018-2022 is sourced from the Google Scholar database. A search for scientific articles was carried out using the Publish or Perish application with the keyword "Martial arts competition" in the article title, category, abstract, key words. The map for the development of the Martial arts competition scientific publication model was analyzed using the VOSViewer application. From the search results using the Publish or Perish application, the maximum number of searches used is 1000 articles, limited to 100 article publications according to the keywords entered, then by type filtering using articles there are 100 papers written in article form. Based on the results and discussion, it can be concluded that there has been a decline every year. In 2018 there were 23% who researched martial arts competition, while in 2019, 2020 and 2021 in the 20% category then in 2022 it will decrease to 17%. on the publication of articles with the keywords Martial Arts Competition in the 2018-2022 period on the Google scholar database